CIM automation in a semiconductor industry - The virtual factory system - Sim, See Hwa. (2008)
This thesis describes the implementation of computer integrated manufacturing (CIM) automation in a Semiconductor Assembly and Test facility. The focus is on the enterprise vision of a Virtual Factory System (VFS) namely factory wide equipment SEMI Equipment Communication Standard/Generic Equipment Model (SECS/GEM) system connectivity and factory wide Automated Material Handling System (AMHS) implementation. (Professor Sivakumar)